Mastering your fellowship - Klaus B. von Pressentin; Mergan Naidoo; Wilhelm J. Steinberg; Lushiku Nkombua; Tasleem Ras (South African Family Practice)
The series, ‘Mastering your Fellowship’, provides examples of the Different question formats encountered in the written and clinical examinations, that is, Part A of the Fellowship of the College of Family Physicians of South Africa (FCFP [SA]) examination. The series is aimed at helping family medicine registrars prepare for this examination.